Eklektisisme Tasawuf: Metamorfosis Sufisme dan Relevansinya dengan Tarekat Modern - Amir Maliki Abitolkha (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2016)
Among the background of the emergence of Sufism is the Muslim struggle against the contestation and power struggle of the Umayyads in the second century Hijri. The problems of power, politics and religious conflicts that gave birth to a pragmatic and materialist attitude by some Muslims were then addressed by some ascetics by voicing an ascetic attitude towards such matters. After developing and splitting into several tarekat, the ideological values of Sufism also changed and shifted and even led to the path of the ideology of Sufism. This shift is what this research wants to uncover, considering how important it is to explain the pure ideology of Sufism by presenting historical and contextual studies as a shield for worldly conflicts and power. By using literature research, this article concludes that the style of Sufi teaching that adheres to the eclecticism model has historical roots as a balance between the profane and the secular. The eclectic Sufi style contains three basic principles of Sufi teachings, namely realizing worldly life as an undeniable reality, spiritual practice rituals such as remembrance and relying on sharia. In addition, Sufi teachings with an eclectic style have a strong level of relevance to religious patterns in Indonesia, the pattern of Sunnī madhhab.